Metabolic cost of external work: a novel CPET parameter optimises characterisation of exercise performance in obese individuals - Jennifer J. Rayner; Rebecca R. Chamley; Robert Barker Davies; Oliver O’Sullivan; Peter Ladlow; Alex N. Bennett; Edward D. Nicol; Oliver J. Rider; David A. Holdsworth (European Journal of Applied Physiology, 2026)
Purpose Both obesity and cardiorespiratory fitness are crucial determinants of symptoms and prognosis. However, interpreting the gold-standard cardiopulmonary exercise test (CPET) is complicated by increasing body size and varying body composition. We hypothesised that the ‘metabolic cost of external work’ (or oxygen uptake (ml/min)/workload (Watts); V̇O 2 /W), a body weight-independent determinant of endurance capacity, would reflect metabolic health more accurately than V̇O 2 alone. Methods A test cohort of 160 fit individuals underwent anthropomorphic and metabolic assessment, maximal bicycle ergometer CPET, and six-minute walk test (6MWT). V̇O 2 /W was calculated at VT1 and peak. The performance of V̇O 2 /W was validated in 62 older, less fit individuals, undergoing the same protocol. 24 obese volunteers were assigned a weight loss intervention, and the impact on V̇O 2 /W examined. Results In both test and validation cohort, V̇O 2 /W at VT1 and peak correlated with 6MWT distance, more strongly than standard CPET parameters. Including V̇O 2 /W improved the accuracy of predicting 6MWT distance. V̇O 2 /W correlated with BMI, insulin sensitivity and waist-to-hip ratio. Metabolic cost falls with weight loss, in parallel to metabolic and functional improvements, in contrast to other CPET parameters. Conclusion Metabolic cost is strongly associated with functional capacity and metabolic health across a range of body weight and fitness, outperforming standard CPET metrics. It is a simple measure which may improve our assessment of the extent to which exertional symptoms are determined by metabolic factors in an individual, and thereby target the most appropriate intervention to those who will benefit most. Graphical Abstract